Assessment of Heat Flux Prediction Capabilities of Residual Distribution Method: Application to Atmospheric Entry Problems (Communications in Computational Physics, 2018)
In the present contribution we evaluate the heat flux prediction capabilitiesof second-order accurate Residual Distribution (RD ) methods in the context of atmospheric(re-)entry problems around blunt bodies. Our departing point is the computationof subsonic air flows (with air modeled either as an inert ideal gas or as chemicallyreacting and possibly out of thermal equilibrium gas mixture) around probe-like geometries,as those typically employed into high enthalpy wind tunnels. We confirmthe agreement between the solutions obtained with the RD method and the solutionscomputed with other Finite Volume (FV ) based codes.However, a straightforward application of the same numerical technique to hypersoniccases involving strong shocks exhibits severe deficiencies even on a geometry assimple as a 2D cylinder. In an attempt to mitigate this problem, we derive new variantsof RD schemes. A comparison of these alternative strategies against establishedones allows us to derive a diagnose for the shortcomings observed in the traditionalRD schemes.